2020
DOI: 10.1111/gcbb.12715
|View full text |Cite
|
Sign up to set email alerts
|

Comparative environmental and economic life cycle assessment of biogas production from perennial wild plant mixtures and maize (Zea mays L.) in southwest Germany

Abstract: Maize silage is the main biogas co‐substrate in Germany, but its use is often questioned due to negative environmental impacts. Perennial wild plant mixtures (WPM) are increasingly considered alternatives, as these extensive systems improve soil quality and enhance agrobiodiversity. Methane yields per hectare however do not match those of maize. This study examined whether the potential advantages of replacing maize with WPM for biogas production are counteracted by lower yields and associated effects. Life cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…The most important is the amount of carbon sequestered during the cultivation period ( carbon_seq ). This can vary widely and greatly depends not only on site‐specific conditions (McCalmont et al, 2017) but also on the methodological approach selected for carbon accounting (Goglio et al, 2015) and the (assumed) permanence of the carbon sequestered (Lask, Martínez Guajardo, et al, 2020; Lask, Rukavina, et al, 2020). Due to the high variability in the possible values that this parameter can take, it is left to the user which value to select.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important is the amount of carbon sequestered during the cultivation period ( carbon_seq ). This can vary widely and greatly depends not only on site‐specific conditions (McCalmont et al, 2017) but also on the methodological approach selected for carbon accounting (Goglio et al, 2015) and the (assumed) permanence of the carbon sequestered (Lask, Martínez Guajardo, et al, 2020; Lask, Rukavina, et al, 2020). Due to the high variability in the possible values that this parameter can take, it is left to the user which value to select.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, industry's interest in miscanthus has grown due to its possible usage in a range of applications. It has been shown that miscanthus biomass can be used for the production of insulation material and chemicals, and can also serve as a bioenergy feedstock (Lask, Martínez Guajardo, et al, 2020; Lask, Rukavina, et al, 2020; Moll et al, 2020; Wagner et al, 2017). Each of these application pathways has been considered in environmental sustainability assessments, which commonly rely on the life cycle assessment (LCA) methodology (Kiesel et al, 2017; Lask et al, 2019; Wagner & Lewandowski, 2017; Wagner et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The life cycle energy consumption and global warming potential of 1 MJ of gasoline and diesel production utilising switchgrass and pine residues were observed as 0.7 to 1.1 MJ and 43.2 to 76.6 g CO 2 eq, respectively Lask et al (2020) Global warming potential When considering land-use scenarios due to maize silage and wild energy crop production, blended feedstock consisting of both showed the lowest global warming potential as 198 kg CO 2 eq/kWh of electricity produced Mendecka et al (2020) Global warming, acidification, eutrophication and For treatment and upgrade of 1 kg of olive pomace, following impacts were observed freshwater ecotoxicity potentials Global warming potential = 0.468 to 1.024 kg CO 2 eq…”
Section: Uncertainty Scenario and Sensitivity Analysismentioning
confidence: 99%
“…Both dLUC and iLUC can have highly influential effects on environmental performances, especially when considering an increased future demand for bio-based products. In fact, it was shown, for example, in a study evaluating different agricultural substrates for biogas production, that dLUC can decrease the total GWP up to 50% while iLUC can increase it by between approximately 16% and 31% (Lask et al, 2020). To minimize adverse effects from dLUC and iLUC, cultivation on marginal land should be prioritized where less or no competition with food crops is expected (Lewandowski et al, 2016).…”
Section: Validation Of Comparability and Limitationsmentioning
confidence: 99%